Cognitive behavior and human computer interaction based on machine learning algorithm - Kumar, Sandeep (Professor of computer science and engineering); Raja, Rohit; Tiwari, Shrikant; Rani, Shilpa (Hoboken, NJ : Wiley ; Beverly, MA : Scrivener Publishing, 2021)
COGNITIVE BEHAVIOR AND HUMAN COMPUTER INTERACTION BASED ON MACHINE LEARNING ALGORITHMS The objective of this book is to provide the most relevant information on Human-Computer Interaction to academics, researchers, and students and for those from industry who wish to know more about the real-time application of user interface design. Human-computer interaction (HCI) is the academic discipline, which most of us think of as UI design, that focuses on how human beings and computers interact at ever-increasing levels of both complexity and simplicity. Because of the importance of the subject, this book aims to provide more relevant information that will be useful to students, academics, and researchers in the industry who wish to know more about its real-time application. In addition to providing content on theory, cognition, design, evaluation, and user diversity, this book also explains the underlying causes of the cognitive, social and organizational problems typically devoted to descriptions of rehabilitation methods for specific cognitive processes. Also described are the new modeling algorithms accessible to cognitive scientists from a variety of different areas. This book is inherently interdisciplinary and contains original research in computing, engineering, artificial intelligence, psychology, linguistics, and social and system organization as applied to the design, implementation, application, analysis, and evaluation of interactive systems. Since machine learning research has already been carried out for a decade in various applications, the new learning approach is mainly used in machine learning-based cognitive applications. Since this will direct the future research of scientists and researchers working in neuroscience, neuroimaging, machine learning-based brain mapping, and modeling, etc., this book highlights the framework of a novel robust method for advanced cross-industry HCI technologies. These implementation strategies and future research directions will meet the design and application requirements of several modern and real-time applications for a long time to come. Audience: A wide range of researchers, industry practitioners, and students will be interested in this book including those in artificial intelligence, machine learning, cognition, computer programming and engineering, as well as social sciences such as psychology and linguistics.
Cognitive Behavior: Different Human-Computer Interaction Types / S Venkata Achyuth Rao, Sandeep Kumar, GVRK Acharyulu -- Classification of HCI and Issues and Challenges in Smart Home HCI Implementation / Pramod Vishwakarma, Vijay Kumar Soni, Gaurav Srivastav, Abhishek Jain -- Teaching-Learning Process and Brain-Computer Interaction Using ICT Tools / Rohit Raja, Neelam Sahu, Sumati Pathak -- Denoising of Digital Images Using Wavelet-Based Thresholding Techniques: A Comparison / Devanand Bhonsle -- Smart Virtual Reality-Based Gaze-Perceptive Common Communication System for Children With Autism Spectrum Disorder / Karunanithi Praveen Kumar, Perumal Sivanesan -- Construction and Reconstruction of 3D Facial and Wireframe Model Using Syntactic Pattern Recognition / Shilpa Rani, Deepika Ghai, Sandeep Kumar -- Attack Detection Using Deep Learning-Based Multimodal Biometric Authentication System / Nishant Kaushal, Sukhwinder Singh, Jagdish Kumar -- Feature Optimized Machine Learning Framework for Unbalanced Bioassays / Dinesh Kumar, Anuj Kumar Sharma, Rohit Bajaj, Lokesh Pawar -- Predictive Model and Theory of Interaction / Raj Kumar Patra, Srinivas Konda, M Varaprasad Rao, Kavitarani Balmuri, G Madhukar -- Advancement in Augmented and Virtual Reality / Omprakash Dewangan, Latika Pinjarkar, Padma Bonde, Jaspal Bagga -- Computer Vision and Image Processing for Precision Agriculture / Narendra Khatri, Gopal U Shinde -- A Novel Approach for Low-Quality Fingerprint Image Enhancement Using Spatial and Frequency Domain Filtering Techniques / Mehak Sood, Akshay Girdhar -- Elevate Primary Tumor Detection Using Machine Learning / Lokesh Pawar, Pranshul Agrawal, Gurjot Kaur, Rohit Bajaj -- Comparative Sentiment Analysis Through Traditional and Machine Learning-Based Approach / Sandeep Singh, Harjot Kaur -- Application of Artificial Intelligence and Computer Vision to Identify Edible Bird's Nest / Weng Kin Lai, Mei Yuan Koay, Selina Xin Ci Loh, Xiu Kai Lim, Kam Meng Goh -- Enhancement of Satellite and Underwater Image Utilizing Luminance Model by Color Correction Method / Sandeep Kumar, E G Rajan, Shilpa Rani.
Includes bibliographical references and index.
Online resource; title from PDF title page (John Wiley, viewed December 13, 2021).
John Wiley and Sons
Keywords: Human-computer interaction; Human-computer interaction